Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acs.energyfuels.3c00875
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Looping Dry Reforming of Methane over Ni-Modified WO3/ZrO2: Cooperative Work of Dispersed Tungstate Species and Ni over the ZrO2 Surface

Abstract: In this study, we successfully developed nickel (Ni)-modified tungstate zirconia (Ni/WO3/ZrO2) as an effective material for chemical looping dry reforming of methane (CL-DRM) under isothermal conditions (750 °C). The performance of Ni/WO3/ZrO2 strongly depended on the WO3 loading amount. The optimal amount of 10.0 wt% WO3, corresponding to low surface W density (<4 W atoms/nm2), in Ni/WO3(10)/ZrO2 resulted in the exclusive formation of dispersed tungstate species, such as isolated monotungstate and/or oligomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…XAS data were measured in transmission mode, and the Ir foil was used as a reference. The data obtained from XAS were processed using the ATHENA software …”
Section: Methodsmentioning
confidence: 99%
“…XAS data were measured in transmission mode, and the Ir foil was used as a reference. The data obtained from XAS were processed using the ATHENA software …”
Section: Methodsmentioning
confidence: 99%
“…Ni-based OCs are often applied in the CLC due to their high catalytic activity for carbon-based fuel gases such as CH 4 . Studies have shown that the conversion rate of NiO-Fe 2 O 3 /La 0.8 Sr 0.2 FeO 3 to CH 4 in the CLDR reached 97%, and the conversion rate of CO 2 to CO exceeds 90%, which was ascribed to the addition of NiO increasing the crystallinity of Fe 2 O 3 and the formation of NiFe 2 O 4 .…”
Section: Oxygen Carriersmentioning
confidence: 99%
“…The catalyst can confine the inner Ni nanoparticle by the external shell, and the small size of Ni nanoparticles can be preserved for fast carbon gasification. The advantages of Ni sintering limitation and carbon deposit reduction positively improve the stability of DRM. Therefore, as an important type and stable catalyst, it is necessary to review the development of confined Ni catalysts for DRM.…”
Section: Introductionmentioning
confidence: 99%